2021
DOI: 10.1002/14651858.cd013853
|View full text |Cite
|
Sign up to set email alerts
|

Exergaming for dementia and mild cognitive impairment

Abstract: To assess the e ects of exergame applications on physical and cognitive outcomes, and activities of daily living (ADL), in people with dementia and mild cognitive impairment (MCI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Exergames. These are video games that promote (either via using or requiring) players' physical movements (exertion) that is generally more than sedentary and includes strength, balance, and flexibility activities [97]. Examples of studies that used this type of training are [74,82,83].…”
Section: Moderators Of Vr Efficacymentioning
confidence: 99%
“…Exergames. These are video games that promote (either via using or requiring) players' physical movements (exertion) that is generally more than sedentary and includes strength, balance, and flexibility activities [97]. Examples of studies that used this type of training are [74,82,83].…”
Section: Moderators Of Vr Efficacymentioning
confidence: 99%
“…These are major healthcare data bases with an excellent cover of VR and ADHD interventions literature which were used in similar studies (e.g. Bahar‐Fuchs et al 2019 ; Voinescu et al 2021a ). At full-text screening, the list of references of the records was screened independently by two researchers (NC and AV) to detect any other relevant studies that did not appear in the initial database search.…”
Section: Methodsmentioning
confidence: 99%
“…The type of control group can be a significant moderator as in the medical literature type of control group may produce different effects on the outcomes and is analysed accordingly (e.g. Bahar‐Fuchs et al 2019 ; Voinescu et al 2021a ). For example, in the VR literature, Fodor et al ( 2018 ) identified that type of control group was a significant moderator of effect size in a previous meta-analysis investigating the effectiveness of VR interventions on the severity of anxiety and depression (Fodor et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…There were no baseline differences between intervention groups (see Table 1) to suggest a problem with the randomisation process. As in other VR-based studies, blinding of participants and personnel was not possible (Voinescu et al, 2021); however, participants were blinded to study aim. Because this was a one-session procedure and in line with our University regulations in response to Covid-19 in order to minimise the spread of infections we were not allowed to use two experimenters for one session to interact with the participant and this is why the same experimenter administered the tasks and performed all the assessments.…”
Section: Stress Testmentioning
confidence: 99%